PHYSIOTHERAPY MANAGEMENT FOR PRE-OPERATIVE ANTERIOR CRURIATE LIGAMENT INJURY: A CASE REPORT - Anjoni, Martina Dwi; Susilo, Taufik Eko (Universitas Muhammadiyah Surakarta, 2021)
Introduction : Previous studies have shown that preoperative management of ACL injuries performed at least 3 weeks before surgery can improve postoperative recovery, prevent knee joint effusion, can be fully active and passive range-of-motion, and increase quadriceps muscle strength with strengthening exercises. Case Presentation : A 19-year-old man as an athlete complains of pain in the right knee. The patient reported that the onset of the pain complaint was that in March the patient fell on the stairs with his feet sideways out. After the incident the patient felt pain, swelling and bruising in the right knee area. The results of Magnetic Resonance Imaging (MRI) carried out on May 20, 2021 showed a complete Anterior Cruciate Ligament (ACL) rupture. Management and Outcome : Ultrasound and strengthening exercise with the aim of increasing and maintaining the muscle strength of the lower limbs in preparation before surgery, reducing pain during walking activities and preventing further back pain. Evaluation of pain using VAS and muscle strength using MMT. Discussion : In this case, prior to surgery or reconstruction, a pre-operative rehabilitation program for ACL injuries was given with the aim of focusing on quadriceps strength, reducing pain for normal gait and ADL. Conclusion : Pre-operative physiotherapy management of ACL injuries found an increase in muscle strength in the quadriceps and hamstring muscles. But in pain management there is no reduction in pain during walking activities.